Evaluating the Effect of the Demographic, Trichoscopic and Laboratory Characteristics on The Recurrence of Alopecia Areata - Didem Kazan (Dermatology Practical & Conceptual, 2024)
Introduction: Alopecia areata (AA) has diverse disease characteristics and multiple factors may interfere with the prognosis of the disease.